ANALYSIS OF AUDIT QUALITY FACTORS: THE EFFECT OF AUDIT FEES, AUDIT TENURE, PUBLIC ACCOUNTING FIRM SIZE, AND AUDIT COMMITTEES IN MANUFACTURING SECTOR OF THE INDONESIA STOCK EXCHANGE (2018 – 2022) - Mercyana Amelia Putri; Novita Weningtyas Respati (Universitas Muhammadiyah Bengkulu, 2025)
Audit quality is the auditor’s effectiveness in finding and disclosing material inconsistencies in the client’s financial statements. Measured by using absolute discretionary accruals. This study aims to empirically test and analyze the effect of audit fees, audit tenure, size of public accounting firm, and audit committees on audit quality in manufacturing sector companies listed on the Indonesia Stock Exchange in 2018-2022. This type of research is quantitative with causality approuch. The study population amounted to 198 with sampling using purposive sampling methods, so that the total sample tested was 335. Statistical tests were carried out using multiple linear regression analyses method using SPSS. The result indicate that audit fees have a positive effect on audit quality, while audit tenure, size of public accounting firm, and audit committee do not have a significant effect on audit quality